The Familial Occurrence of Obstructive Sleep Apnoea Syndrome (OSAS) - Bielicki, Piotr; Przybylowski, Tadeusz; Chazan, Ryszarda (Global Journal of Respiratory Care, 2014)
The aim of the study was to compare the incidence of obstructive sleep apnoea/hypopnoea syndrome (OSAS) in relatives of subjects with OSAS and in relatives without OSAS but with clinical symptoms of this disease. The study group consisted of 186 relatives of patients with OSAS and 117 relatives of patients with symptoms of OSAS in whom the disease was not confirmed by polysomnography. They were all mailed a questionnaire with questions concerning anthropometric data, the presence of symptoms typical for OSAS and the presence of concomitant diseases. Analysis of the obtained data revealed an increased frequency of snoring, sleep apnea and nycturia in the relatives of patients with OSAS when compared to relatives of patients without OSAS, but the difference was not statistically significant. The incidence of daytime OSAS symptoms was significantly higher in the group of relatives of patients with OSAS. No differences in the incidence of arterial hypertension, ischemic heart disease and diabetes mellitus were found. In order to confirm the presence of OSAS in family members with typical symptoms, we performed polysomnography. Were diagnosed OSAS in 20 (29.4 %) relatives of patients with OSAS and only in 8 (18.2) relatives of patients without OSAS. These results confirm the increased incidence of OSAS in patients with a family history of this disease.